The project “ROCK-ME: Geochemical response of Alpine Rock Glaciers to global warming: hydroecological consequences of trace element Export” - Bruno, M. C.; Tolotti, M.; Brighenti, S.; Comiti, F.; Brusetti, L.; Fisher, A. (2022)
ROCK-ME is a 3-year project funded by the 4th Call of the EUREGIO Interregional Project Networks framework, started on April 1st 2022. The project addresses the effects of climate change on the degradation of mountain permafrost. Thawing rock glaciers (RG) are becoming major hydroecological drivers in numerous deglaciating Alpine catchments, as RG export cold waters often enriched in trace elements (TE). However, both the hydrological drivers and the ecological effects of TE enrichment on RG-fed streams and on the downstream river networks are almost entirely unknown. The research questions investigated by ROCK-ME are: 1) Thawing RG export higher loads of TE than glaciers, relict RG and groundwater springs; 2) TE in RG-streams mainly originate from bedrock weathering, and a smaller amount derives from past/present atmospheric deposition; 3) TE export and its ecological effects vary at multiple timescales in relation to seasonal and long-term dynamics of permafrost thawing; 4) TE bioaccumulate in the stream foodweb; 5) RG microbial communities influence TE bioavailability and toxicity; 6)thawing RG release heavy metal resistance genes. Three Alpine catchments with different proportions of glaciers and RG cover will be investigated with an integrated approach combining geomorphological/geochemical analysis, hydrological monitoring and modelling, ecological and genomic characterization.